Respuesta :

[tex]y=x(\arctan x)^{1/2}[/tex]

Use the product rule first:

[tex]\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{\mathrm dx}{\mathrm dx}(\arctan x)^{1/2}+x\dfrac{\mathrm d(\arctan x)^{1/2}}{\mathrm dx}[/tex]

[tex]\dfrac{\mathrm dy}{\mathrm dx}=(\arctan x)^{1/2}+x\dfrac{\mathrm d(\arctan x)^{1/2}}{\mathrm dx}[/tex]

Use the chain rule to compute the derivative of [tex](\arctan x)^{1/2}[/tex]. Let [tex]z=(\arctan x)^{1/2}[/tex] and take [tex]u=\arctan x[/tex], so that by the chain rule

[tex]\dfrac{\mathrm dz}{\mathrm dx}=\dfrac{\mathrm dz}{\mathrm du}\dfrac{\mathrm du}{\mathrm dx}[/tex]

[tex]\dfrac{\mathrm dz}{\mathrm du}=\dfrac{\mathrm du^{1/2}}{\mathrm du}=\dfrac12u^{-1/2}[/tex]

[tex]\dfrac{\mathrm du}{\mathrm dx}=\dfrac{\mathrm d\arctan x}{\mathrm dx}=\dfrac1{1+x^2}[/tex]

[tex]\implies\dfrac{\mathrm d(\arctan x)^{1/2}}{\mathrm dx}=\dfrac1{2(\arctan x)^{1/2}(1+x^2)}[/tex]

So we have

[tex]\dfrac{\mathrm dy}{\mathrm dx}=(\arctan x)^{1/2}+\dfrac x{2(\arctan x)^{1/2}(1+x^2)}[/tex]

You can rewrite this a bit by factoring [tex](\arctan x)^{-1/2}[/tex], just to make it look neater:

[tex]\dfrac{\mathrm dy}{\mathrm dx}=\dfrac1{2(\arctan x)^{1/2}}\left(2\arctan x+\dfrac x{1+x^2}\right)[/tex]

ACCESS MORE